ARAHAN PENGELOLAAN BLOK PEMANFAATAN KESATUAN PENGELOLAAN HUTAN LINDUNG (KPHL) UNIT VI PADA AREAL MODEL MIKRO DAS (MDM) TALAWAAN - Zaini, Badrun ,.; Polii, Bobby Vian Jhon; Walangitan, Hengki Djemie (AGRI-SOSIOEKONOMI, 2019)
This study aims to: (1) Analyze management models with Geographic Information Systems (GIS), (2)Â Arrange alternative directions for priority management with a combination of GIS and Analytical Hirarchy Process (AHP) and policy direction of land tenure in forest areas that are in the utilization block KPHL UnitÂ VI which is in Talawaan MDM. The method used in this study is a survey method, namely: a method for obtaining field data by means of systematic observation, measurement and recording of the object under studyÂ and supported by the results of laboratory analysis. Sampling and field measurements are carried out usingÂ strata techniques with consideration to adjusting the location of the collection. Analysis of the data used: a)Â Estimating the amount of erosion using the formula Universal Soil Loss Equation (USLE), b) The combinationÂ of Geographic Information Systems and Analytical Hierarchy Process (AHP) is used to prepare alternativesÂ for decision making. The results of this study indicated that the Management Model formed in the study area isÂ the Community Forest Management Model (HKm) and Community Plantation Forest (HTR) and with aÂ management period of 35 years and can be extended thereafter. Furthermore, the direction of managementÂ priorities according to AHP analysis with economic, ecological and social targets is to implement aÂ management model with Land Utilities Type (LUT) Agrorestry, enrichment LUT and reforestation LUT withÂ an economic target value of 429 points, ecological target value of 143 points and weight social target value ofÂ 429 points. The direction of the Government’s policy for the completion of land tenure in this forest area is toÂ provide management access to forest areas in the form of Social Forestry Program with the Community ForestÂ Management Model (HKm) and Community Plantation Forest (HTR).*eprm*